2021
DOI: 10.3390/jcm10132742
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Ureteroscopy and Laser Stone Fragmentation (URSL) for Kidney Stone Disease (KSD): Comparative Cohort Study Using MOSES Technology 60 W Laser System versus Regular Holmium 20 W Laser

Abstract: Background: For ureteroscopy and laser stone fragmentation (URSL), the use of laser technology has shifted from low power to higher power lasers and the addition of Moses technology, that allows for ‘fragmentation, dusting and pop-dusting’ of stones. We wanted to compare the outcomes of URSL for Moses technology 60 W laser system versus matched regular Holmium 20 W laser cases. Methods: Prospective data were collected for patients who underwent URSL using a Moses 60 W laser (Group A) and matched to historical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 26 publications
0
26
1
1
Order By: Relevance
“…In-vitro and in-vivo studies have found that MOSES technology improves significantly the ablation rate, reduces retropulsion [9] and improves the pop-corn noncontact lithotripsy technique [10]. In clinical practice using MOSES laser technology reduces significantly the operative time [11] and improves the stone-free rate [12 ▪ ,13].…”
Section: Laser Technologiesmentioning
confidence: 99%
“…In-vitro and in-vivo studies have found that MOSES technology improves significantly the ablation rate, reduces retropulsion [9] and improves the pop-corn noncontact lithotripsy technique [10]. In clinical practice using MOSES laser technology reduces significantly the operative time [11] and improves the stone-free rate [12 ▪ ,13].…”
Section: Laser Technologiesmentioning
confidence: 99%
“…In two URS studies, Moses 1.0 was compared to the regular mode of a LP Ho:YAG laser [ 18 , 19 ]. The LP Ho:YAG lasers used in these studies were the Dornier Medilas ® H20 [ 18 ] and the Lumenis Holmium 20 W laser [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“… Forest plot of the meta-analysis comparing post-operative complications between Moses versus regular pulse modulation [ 18 , 35 , 37 , 38 ]. …”
Section: Figurementioning
confidence: 99%